Identifikasi Drug Related Problems Terhadap Pasien Hipertensi Di Rumah Sakit Royal Prima Marelan - Yohanes Dewantoro Situmorang; Razoki, Razoki; Novitaria Br Sembiring (CV. ITTC INDONESIA, 2025)
This study aims to assess Drug Related Problems (DRPs) in hypertensive patients hospitalized at Royal Prima Marelan General Hospital during the period January until June 2024. The study was conducted as a descriptive retrospective analysis on 33 patients using medical records and prescription data. The results showed that drug interactions were the most common DRPs (98,51%), with 64 cases classified as moderate severity, 37 as minor, and 12 as major. The most common interactions occurred with the combination of amlodipine and clopidogrel, while major interactions occurred with the combination of candesartan and spironolactone. Regular monitoring of potential drug interactions is crucial to support the safety and effectiveness of treatment.